MULTIMODAL REPRESENTATIONS ACROSS SCIENTIFIC GENRES: PERSPECTIVES FROM SCIENCE TEACHERS' PRACTICES - Padios, Alfredo; Pascua, Sarah; Orleans, Antriman (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2023)
Multimodal representations have caught science education researchers’ attention due to its immense role in meaning making. While much have been written about this area of research, the interplay between multimodal representations and scientific genres in classrooms is yet to be fully explored.The purpose of this study is to examine multimodal representations across scientific genres from the viewpoints of science teachers. With Filipino science teachers as respondents, we employed a sequential explanatory mixed methods research design to determine the frequency of occurrence of scientific genres in classrooms as well as the frequency of use of multimodal representations across each scientific genre. First, we administered the questionnaire, analyzed the result then conducted a follow-up interview to determine how and why scientific genres and multimodal representations are utilized. Results revealed that information report and explanation are the genres most utilized by science teachers primarily because they conform to curriculum standards and that these support students’ learning and skills. On the other hand, experimental account and argument genres are used less often largely due to lack of available materials and teacher competence. Across these genres, linguistic-verbal, visual-graphical and gestural-kinesthetic representations are “always” used while material-operational and mathematical-symbolic are used to a lesser extent. More importantly, this study confirms again that science teaching is multimodal mainly to address each student learning needs and make meaning making thus, science learning, easier. Important implications to practice and research are discussed.